Annual linear growth velocities of preschool children by age and sex in the Terai of Nepal: A three-year cohort study. - Manohar, Swetha. (Tufts University. Tisch Library., 2019)
The poster was presented in ASN 2018.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy